BASOCELLULAR CARCINOMA OF THE EXTERNAL EAR CANAL - CASE REPORT - Branco, Carla (2006)
Basocellular carcinoma (BCC) is a relatively common skin malignancy. Since its etiopathogenesis is related to prolonged sun exposure, the external nose and the auricular region are potential risk areas, a reason why ENT specialists should be familiar with this entity.The authors present the case of a recurring auricular BCC with invasion of external auditory canal, submitted to a lateral temporal bane resection with superficial parotidectomy.Concerning the aggressiveness of the auricular BCC the resection should be large, independently the functional and aesthetic consequences.